MULTIVARIATE ANALYSIS OF THE IMPACT OF MIGRATION ON THE SOCIO-ECONOMIC DEVELOPMENT OF REGIONS - Nina A. Eldyaeva; Ekaterina S. Kovanova (Статистика и экономика, 2016)
Internal labor migration has a significant impact on the socio-economic development of the provinces. The article analyzes the impact of migration on the development level of giving and receiving regions. Using cluster analysis segmentation of the regions on the impact of migration on the socio-economic development of regions was made in the article.